A Corpus-based Analysis of Job Description Discourse: A Corpus-based Analysis of Job Description Discourse - Quan, Jiuding (International Journal of Linguistics and Translation Studies, 2023)
This research applies a corpus discourse analysis approach to examine 160 job descriptions specific to the translation profession published in Shanghai in May 2023. Job descriptions (JDs) include educational backgrounds, experience requirements, and knowledge skills. By utilizing corpus data, the study investigates the linguistic characteristics of translation job descriptions and the job market demand for translation graduates. This study indicates that graduates who are only capable of translating languages are less likely to enter the language service industry. In addition, there is a significant disparity between the current supply of translation graduates and job market demand. The demand of the job market for translation graduates should have talented language ability, solid industrial knowledge, and multidimensional competencies. This study provides valuable information to universities offering translation majors, enabling them to develop curriculums that are aligned with industry needs, educate translation graduates who are well-suited for the job market, and provide support to translation graduates in order to facilitate their professional growth and efficient employment.